2007
DOI: 10.1097/fjc.0b013e3180cab12e
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Ginsenoside Rb1 on Human Umbilical Vein Endothelial Cells In Vitro

Abstract: Ginseng has beneficial effects on the cardiovascular system, but its underlying mechanism is unclear. This study investigated the effects of ginsenoside Rb1, a major constituent of ginseng, on the changes of lactate dehydrogenase (LDH) activity, nitric oxide (NO), tissue-type plasminogen activator (t-PA), and plasminogen activator inhibitor-1 (PAI-1) in oxidized low-density lipoprotein (oxLDL)-injuring endothelial cells. Human umbilical vein endothelial cells were cultured and divided into 6 groups (n = 6): co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 34 publications
0
37
2
Order By: Relevance
“…It was also shown to abate homocysteine-induced endothelial dysfunction by increasing NO production and eNOS phosphorylation via PI3K/Akt activation and PKC inhibition [16]. Ginsenoside Rb1 had protective effects on oxLDL-injuring human vascular endothelial cells by increasing NO production and eNOS mRNA expressions [14]. Although these results appear to contradict our results, it is possible that regulation of NOS/NO signal by ginsenoside Rb1 varies in different pathological conditions.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…It was also shown to abate homocysteine-induced endothelial dysfunction by increasing NO production and eNOS phosphorylation via PI3K/Akt activation and PKC inhibition [16]. Ginsenoside Rb1 had protective effects on oxLDL-injuring human vascular endothelial cells by increasing NO production and eNOS mRNA expressions [14]. Although these results appear to contradict our results, it is possible that regulation of NOS/NO signal by ginsenoside Rb1 varies in different pathological conditions.…”
Section: Discussioncontrasting
confidence: 56%
“…Ginsenoside Rb1 inhibited the expression of TNF-α, IL-1β and IL-6 in lipopolysaccharide (LPS) -stimulated murine peritoneal macrophages [13]. Although release of NO by ginsenoside Rb1 may underlie the cardiovascular protection [14], the effects and mechanisms of ginsenoside Rb1 on NO production by chondrocytes during inflammatory conditions are not clear. Thus, the purpose of this study was to investigate the effect of ginsenoside Rb1 on NO production, iNOS expression and NF-κB activation in IL-1β-stimulated SW1353 chondrosarcoma cells.…”
Section: Introductionmentioning
confidence: 96%
“…OxLDL can also induce increased production of intracellular ROS and apoptosis by binding to lectin-like oxLDL receptor-1 (65, 72). OxLDL also affects the expression of various key genes in endothelial cells, thus altering endothelial function (126). In addition, oxLDL can also induce cytoskeletal rearrangements such as F-actin distribution, cell contraction, and the formation of intercellular gaps (92,364).…”
Section: B Oxldl Is One Of the Most Important Risk Factors For Athermentioning
confidence: 99%
“…Some papers had reported that ginsenoside Re can protect cardiomyocytes from oxidant injury induced by both exogenous and endogenous oxidants through scavenging H 2 O 2 and hydroxyl radicals (35). Ginsenoside Rb1 has been shown to protect against myocardial-reperfusion injury by enhancing the expression of eNOS and increasing the content of NO as well as inhibiting oxidative stress and protecting the endothelial cells (36,37). Ginsenoside Rg1 has been reported to promote endogenous NO production, prolong ventricular refractoriness and repolarization, and inhibit left ventricular (LV) hypertrophy in rats (38).…”
Section: Discussionmentioning
confidence: 99%